Tandem reef restoration using corals and sea urchins: Building complex habitat for herbivores - Catherine Lachnit; Emily Esplandiu; Joshua Patterson; Diego Lirman (PLoS ONE, 2025)
Amidst the decline of coral reef ecosystems, restoration practitioners are expanding their focus to incorporate key reef community components, such as grazers, to improve site conditions and the long-term survivorship of restored corals. We investigated the use of hatchery-propagated Diadema antillarum as well as two other locally abundant urchin species, Lytechinus variegatus and Echinometra viridis, for coral-urchin tandem reef restoration in Florida, USA. Urchins were deployed onto reef plots at various stages of Acropora cervicornis restoration and provided artificial cement refuges to evaluate retention and herbivory rates. Retention of urchins was low and variable among species. After 42 days, retention was 22% for E. viridis, 7% for D. antillarum, and 0% for L. variegatus. Retention was influenced by plot complexity (restoration state) and was significantly higher in high-complexity plots for D. antillarum and E. viridis. Within plots, refuge types did not have a significant influence on urchin retention. A reduction in macroalgal cover was only observed on plots with relocated E. viridis when densities were maintained > 0.4 urchins m-2. A second deployment of D. antillarum, with urchins caged for a month prior to release, resulted in significantly higher urchin retention. Within cages, grazing and the consumption of coral tissue were influenced by urchin density. At low urchin densities (4 urchins m-2) macroalgae cover remained high and corals were overgrown by algae. At intermediate densities (12 urchins m-2) algae were reduced and the growth of corals was maximized. At the highest densities (40 urchins m-2), algal cover was reduced but urchins caused tissue mortality as a result of over-grazing, highlighting the importance of maintaining relocated urchins at adequate densities to maximize the benefits of tandem restoration. Thus, if retention can be improved and urchins maintained at intermediate densities, the tandem restoration of corals and sea urchins could increase the efficacy of reef restoration.